Readiness Analysis of Implementation Of Online Ticketing System At Bira France Port, South Sulawesi Province - Febriansyah Febriansyah; Chairul Insani Ilham; Arandho Putra Naghari (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Various methods are used by service users in ordering tickets, either by ordering directly to the counter or to the nearest agent with prospective passengers. Both ordering processes are less effective, both in terms of time and cost. For this reason, it is necessary to have an ordering process to be more effective both in terms of time and cost itself as well as making it easier, more practical and faster, of course, in ordering tickets using the internet. Port operators and service users can be seen from the technological aspect, the willingness aspect, the understanding aspect, and the trust aspect by using digitalization in the application of this online ticket. With full support from the implementation of Ministerial Regulation 19 of 2020 concerning Electronic Ferry Ticket Operators to be implemented at the Bira Ferry Port. Because it provides time efficiency, convenience, convenience for service users with the application of this online ticket.